(untitled) - Nickels, William G. (Englewood Cliffs, N.J., 1982)
This book is well written and provides real world examples for every concept mentioned, which helps me understand everything a little better. Very up to date (as with most management books) and thorough, which helps me since I'm taking my marketing course online and I don't have a teacher face-to-face I can talk to.
Keywords: Marketing,Tiếp thị